Faithful deliberation: rhetorical invention, evangelicalism, and #metoo reckonings - Geiger, T. J. (Rhetoric, culture, and social critique, 2022)
"Investigates the rhetorical practices that contemporary evangelical Christian women use to confront theological and cultural issues that stymie deliberation within their communities regarding how to respond to sexual assault and domestic violence, with an eye toward both compassion for victims and accountability for perpetrators"--